1979
DOI: 10.1161/01.cir.59.5.977
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiovascular responses to static-dynamic effort and dynamic effort alone in patients with chronic ischemic heart disease.

Abstract: Thirty men, mean age 55 years, known to have treadmill-induced ischemic ST-segment depression, performed static and dynamic effort, i.e., forearm lifting and treadmill exercise, separately and combined. Static effort was sustained at 20%, 25% or 30% of maximal forearm lifting capacity. Two symptom-limited treadmill tests, one with and one without added static effort, were performed on each of two visits. Compared with dynamic effort alone, combined static-dynamic effort decreased treadmill work load and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Indeed, it has been suggested that increased subendocardial perfusion secondary to the elevated dBP may actually reduce the risk of ischaemic cardiac responses during this type of exercise. [ 46 ] Furthermore, the magnitude of dBP response observed in the present study, which as indicated earlier might also be representative of previous IE interventions using the same standard protocol, may even act as a specific stimulus for the BP adaptations reported. Indeed, the physiological benefits following a single IE session including improved cardiac autonomic modulation and baroreceptor reflex sensitivity [ 30 ] and cardiac mechanical responses [ 47 ] have been recently reported.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, it has been suggested that increased subendocardial perfusion secondary to the elevated dBP may actually reduce the risk of ischaemic cardiac responses during this type of exercise. [ 46 ] Furthermore, the magnitude of dBP response observed in the present study, which as indicated earlier might also be representative of previous IE interventions using the same standard protocol, may even act as a specific stimulus for the BP adaptations reported. Indeed, the physiological benefits following a single IE session including improved cardiac autonomic modulation and baroreceptor reflex sensitivity [ 30 ] and cardiac mechanical responses [ 47 ] have been recently reported.…”
Section: Discussionsupporting
confidence: 83%
“…Epicardial layers are perfused during diastole as well as during systole, but blood flow to subendocardial layers occurs mostly during diastole [31,32], Increase in the diastolic blood pressure with static exercise may increase myocardial perfusion [19][20][21], but increase in LV diastolic pressure in patients with enlarged heart could decrease coronary flow to the subendocardial layers. As there was no significant difference in diastolic blood pressure between groups 1 and 2 during weight load, in addition to decreased subendocardial coronary flow associated with increased LV end-diastolic volume, a disproportionate shortening of diastole in group 1 may permit further reduction of subendocardial flow.…”
Section: Discussionmentioning
confidence: 99%
“…143 Safely performed submaximal resistance exercise is well tolerated in patients after an uncomplicated MI. 19,20,144 A combination of static and dynamic resistance exercise at submaximal intensities are frequently performed during activities of daily living and the individualization of the exercise prescription based on one's occupation is a critical consideration in the rehabilitation process. 19,20,144 Kelemen and colleagues 145 have shown that circuit weight training resulted in a 24% increase in upper extremity and leg strength with no change in control patients.…”
Section: Cardiovascular Response To Training In Patients With Cardio-mentioning
confidence: 99%